Representation of Phase Behavior of Ionic Liquids Using the Equation of State for Square-well Chain Fluids with Variable Range - 李进龙 何清 何昌春 彭昌军 刘洪来 (Chinese journal of chemical engineering, 2009)
An equation of state （EOS） for square-well chain fluids with variable range （SWCF-VR） developed based on statistical mechanics for chemical association was employed for the calculations of pressure-volume-temperature （pVT） and phase equilibrium of pure ionic liquids （ILs） and their mixtures. The new molecular parameters for 23 ILs were obtained by fitting their experimental density data over a wide temperature and pressure ranges. The mo- lecular parameters of ILs composed of homologous organic cation and an identical anion such as [Cxmim][NTf2] are good linear with respect to their molecular weight, indicating that the molecular parameters of homologous substances, subsequently p VT and vapor-liquid equilibria vapor-liquid equilibria （VLE） can be predicted using the generalized parameter when no experimental data were available. The new set of parameters were satisfactorily used for calculations of the property of solvent and ILs mixture and the solubility of gas in various ILs at low pressure only using one temperature-independent binary interaction parameter.